In vitro germination and cryopreservation technique for long-term pollen conservation of underutilized legume: Grasspea (Lathyrus sativus) - SHANKAR, M; GOWTHAMI, R; TRIPATHI, KULDEEP; DEEPAK, D A; BARPETE, SURENDRA; AGRAWAL, ANURADHA (The Indian Journal of Agricultural Sciences, 2023)
Grasspea (Lathyrus sativus L.) is an underutilized pulse crop which can withstand adverse environmental conditions such as drought, heat, salinity, waterlogging, pest and diseases. To facilitate hybridization studies, pollen cryoconservation was attempted in L. sativus. Among the different media combination tested for in vitro pollen germination, BK medium with 15% sucrose was optimal. Pollen viability was tested at different storage regimes, viz. 25, 4, -20 and -196 ºC at different storage duration (1, 3, 5, 7, 9, 24 h, 1 week, 2 week and 6 months). For long-term pollen cryopreservation, an ideal MC of 14–16% was achieved by desiccating the pollen for 10 min in a laminar air flow (LAF) chamber. Negative correlation was found between pollen viability, storage duration and temperature (25, 4 and -20°C). Cryopreserved (-196°C) pollen showed significantly higher viability compared to all the other storage conditions. The standardized cryoconservation protocol was applied to 20 accessions of Lathyrus sativus for conservation up to six months without loss of pollen viability. Successful fertilization, fruit and seed set was observed in cross combinations attempted using cryoconserved pollen without any incompatibility barriers. Hence, the present protocol can be used for long-term cryoconservation of L. sativus pollen. The development of an effective long-term storage method of Lathyrus sativus pollen ensures the availability of pollen for grasspea breeding throughout the year.